Stability of the Spectral Problem for Dirac Operators - Ercan, Ahu; Panakhov, Etibar (Amer Inst Physics, 2016)
The meaning of the stability problems of differential operators is that when finite numbers of eigenvalues of operator with different potentials coincide, the difference of their spectral functions is estimated. The main aim of the present paper is to show stability spectral problems for one dimensional Dirac operators on a finite interval. The method which is used in this study is defined by Riabushko [7].
International Conference on Numerical Analysis and Applied Mathematics (ICNAAM) -- SEP 23-29, 2015 -- Rhodes, GREECE